2005
DOI: 10.1038/oby.2005.76
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of Pyruvate Dehydrogenase Phosphatase in Obese Subjects is a Defect that Signals Insulin Resistance

Abstract: PICCININI,MARCO, MICHAEL MOSTERT, GIANFRANCESCO ALBERTO, CRISTINA RAMONDETTI, ROSA F. NOVI, PAOLA DALMASSO, AND MARIA T. RINAUDO. Down-regulation of pyruvate dehydrogenase phosphatase in obese subjects is a defect that signals insulin resistance. Obes Res. 2005;13:678 -686. Objective: The objective of this study was to determine whether down-regulation of pyruvate dehydrogenase phosphatase (PDP) is responsible for poorly active pyruvate dehydrogenase (PDH) in circulating lymphocytes (CLs) of obese subjects (Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…Insulin also increases the affinity of PDP1 for Mg 2+ , stimulating its phosphatase activity (56) and thereby increasing the activity of the mitochondrial pyruvate dehydrogenase complex. Interestingly, PDP1 from obese subjects is less active and has reduced affinity for Mg 2+ (57). …”
Section: Discussionmentioning
confidence: 99%
“…Insulin also increases the affinity of PDP1 for Mg 2+ , stimulating its phosphatase activity (56) and thereby increasing the activity of the mitochondrial pyruvate dehydrogenase complex. Interestingly, PDP1 from obese subjects is less active and has reduced affinity for Mg 2+ (57). …”
Section: Discussionmentioning
confidence: 99%
“…Piccinini et al (36) reported downregulation of lymphocyte PDP activity in obese humans. Also, administration of agents that improve glucose homeostasis and insulin sensitivity also increases hepatic PDP activity in rodent models of type-2 diabetes (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphatase 2C, magnesium-dependent, catalytic subunit is a mitochondrial enzyme regulated by insulin. (94) Niemann-Pick disease, type C1 is a lysosomal membrane protein involved in cholesterol trafficking, (95) and, most importantly, in drug resistance by its drug efflux and sequestration. (96) The genes downregulated in the wt-PAI-1-expressing MDA-MB-435 cells were less numerous ( Table 2).…”
Section: Cell Migration and Invasionmentioning
confidence: 99%